Modified Household Scale Onion Peelers - Wati, Sukma; Jamaluddin, Jamaluddin; Lahming, Lahming (Jurnal Pendidikan Teknologi Pertanian, 2019)
ABSTRACTOnion white is a wrong one ingredients Spices are usually have an important function as wrong one ingredients flavorings (spices) in make Cook or as drug traditional , onion white to be mandatory ingredient in the kitchen when cook because of the aroma and taste produced. In processing garlic must go through a stripping process that takes a long time. This study aims to modify and determine the mechanism of device design, the percentage of the results of peeling, not peeling, damaging and the effective capacity of the garlic peeler. This research is in the form of design. he data analysis used in the form of descriptive statistics. The design mechanism starts from the stage of making a frame, installing electric motors, installing a shaft, installing a fan, installing a tube, attaching a rope and installing a tube lock. As for way testing tool that is, weighs a sample of 300 g of ram next sample enter into in tube and pengu pas onion is operated for 1 min, then results peel weighed, for knowing percentage weight on is peeled, not peeled, broken and capacity effective. Based on the results of the test try tool, the average percentage pared to 80%, the percentage not peeled 20%, the broken 0% and the effective tool capacity for the onion 240 g ram / minuteÂ